Sistem Otomatis Penggerak Lesan Tembak Untuk Latihan Teknik Tempur Cepat Dengan Metode PID - Sandhya Sabila; Puput dani Prasetyo adi; Subairi subairi; M Baidlowi (JASIEK (Jurnal Aplikasi Sains, Informasi, Elektronika dan Komputer), 2021)
Rapid fighting techniques are shooting at materials that require concentration, accuracy, readiness and speed of shooting at targets, which must be performed by a VNI soldier. Soldiers should run out to the firing range at 80, 70 and 50 meters and immediately shoot at moving/underwater targets. What the author wants to do is to perform TTC exercises automatically using a DC motor in the PID method, using sensors at each shooting distance to control the motor on Lesan, so that it does not require personnel to move the target to move or lower Lesan, with the aim help avoid loss of personnel in the event of an accident, during training and more efficient execution of exercises.